Department Chair as University Change Agent: A Practitioner-Researcher Leadership Model - Robbie J. Steward Ph.D. (Academic Chairpersons Conference Proceedings, 2019)
This symposium describes the leadership of department chair, who assumes the position as an institutional change agent by implementing strategies associated with leadership using the practitioner-researcher model. Positive outcomes and unanticipated consequences and implications will be discussed.
Keywords: Academic Leadership; Evidence-based practices; Practitioner-Researcher Model